The Dilemma of Authorship in Artificial Intelligence – From the Perspective of Music Copyright (Journal of Intellectual Property Rights (JIPR), 2025)
The rapid advancement in technology and the advent of artificial intelligence has opened a Pandora box of copyright issues. The primary concern is the authorship of AI generated works. While AI generated work does not have any human contribution, the development of AI technology necessitates some form of protection. The impact of AI technology will be felt more on music, which has its own limitations. The limited sets of notes and chord progressions coupled with the rules of music make it difficult for creativity in music. These limitations when juxtaposed with the peculiarities of artificial intelligence make it difficult to draw line between human intervention and technology. While the article calls for a re-definition of copyright law with reference to AI technology, human creativity should not be compromised for technological advancement. The work emphasizes on a separate sui generis legislation as an ideal solution for the ambiguity and discussions surrounding the newly emerged technology.